Digital Storytelling pada Pembelajaran IPS di Sekolah Dasar - Safitri Yosita Ratri (STKIP AL HIKMAH SURABAYA, 2022)
The use of innovative learning media is still especially in elementary school (SD). This will address the problem in Social Science (IPS) which until now still assumed as a tedious lesson and demands memorization, as well as less material in accordance with the development of society again. The solution is to develop Digital Storytelling or known in the Indonesian language as a digital fairy tale. The use of Digital Storytelling for IPS in elementary school, which is one of the objectives is to develop affective aspects of students, will give the meaning that IPS as a subject that is able to improve students' feelings about acceptance, response, assessment, and character development. For students, Digital Storytelling will attract attention so that will be more motivated to learn IPS. Students need to be trained as early as possible in the future to be able to have a high understanding and empathy in facing social problems in their environment.